Toilet Training Age and Factors Affect Timing, Duration and Delayed: A Cross-sectional Study in Hamadan, Iran - Maryam Farhadian; Maryam Khazaei; Hossein Mahjub; Ramin Kahaei (پژوهان)
Background and Objectives: Toilet training (TT) is a demanding experience for both parents and children, as it is considered one of the most crucial developmental tasks during childhood. The study aimed to investigate the start, completion, and duration of TT in the Iranian population while also examining any factors that may be associated with delayed TT. Materials and Methods: Between January and June 2022, a cross-sectional study was conducted among families with children aged 2-6 years who had completed TT no more than 4 months earlier. The survey was conducted through interviews with parents in the pediatricians' waiting room and Urban Health Centers in Hamadan, Iran. Results: The study involved 315 children, with 164 girls and 151 boys, and found that the mean ages for initiation, completion, and duration of TT were 24.01±5.97, 26.91±6.14, and 2.93±2.34 months, respectively. Girls started TT earlier than boys, and the mother's education level, time of mother's presence, and communication with friends and relatives who had children with ages less than 5 years were positively correlated with earlier initiation and completion. Additionally, 42.8% of mothers reported having little or no knowledge regarding TT. Delayed TT (complete TT after 30 months) was found in 21.6% of children and was associated with the child's birth weight, mother's age, educational status, and time of mother's involvement. Conclusion: Given the crucial role and involvement of parents, especially mothers, in TT, it is suggested that educational programs be developed to provide guidance and support to parents. These programs should emphasize the importance of parental involvement and support and provide practical techniques for promoting a child's readiness for TT.